2020
DOI: 10.1097/brs.0000000000003842
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Dysphagia After Subaxial Cervical Spine Surgery

Abstract: Study Design. Prospective observational cohort study. Objective. To prospectively examine dysphagia after subaxial cervical spine surgery. Summary of Background Data. Although dysphagia after anterior cervical spine surgery is common and well-studied, it has rarely been examined in posterior subaxial cervical spine surgery. Methods. This study analyzed 191 consecutive patients (132 male, 59 female; mean age, 64.9 yrs) who underwent subaxial cervical spine surgery for degenerative disease and completed 1 year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The relationship between postoperative dysphagia and sub-axial cervical alignment has not been well investigated. 30,31 Previous research has suggested that an increase in the C2-C7 angle exceeding 5Β°is associated with a higher risk of postoperative dysphagia. 15,30,32,33 In this study, we observed that the dysphagia group had a mean increase in C2-C7 angle of 6.4 9.7Β°.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between postoperative dysphagia and sub-axial cervical alignment has not been well investigated. 30,31 Previous research has suggested that an increase in the C2-C7 angle exceeding 5Β°is associated with a higher risk of postoperative dysphagia. 15,30,32,33 In this study, we observed that the dysphagia group had a mean increase in C2-C7 angle of 6.4 9.7Β°.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical targets of these blocks are the transverse process and its overlaying muscles and interfascial plane. [6][7][8][9][10][11][12][13][14][15][16][17] The cervical transverse process is significantly smaller than the thoracolumbar ones, and the vertebral artery runs in the vertebral canal in proximity to the cervical transverse process. This structure poses a challenge in localizing the needle and increases the risk of vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other ultrasound-guided cervical erector spinae plane (ESP) blocks have been reported for the treatment of cervical postsurgical pain. The anatomical targets of these blocks are the transverse process and its overlaying muscles and interfascial plane 6–17. The cervical transverse process is significantly smaller than the thoracolumbar ones, and the vertebral artery runs in the vertebral canal in proximity to the cervical transverse process.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of functional status, Japanese Orthopedic Association (JOA), Neck Disability Index (NDI) ( 12 ), and the neck Visual Analogue Scale (VAS) pain scores were used. The prevalence of dysphagia was determined by utilizing the Bazaz system ( Table 1 ) ( 13 ).…”
Section: Methodsmentioning
confidence: 99%